The Analysis of the Intra EU-28 Agri – Food Trade in the Context of the EU Internal Policies - Oksana KIFORENKO; Nataliia VASYLIEVA; Sergii PRYLIPKO; Oleksandra VASYLIEVA (Communications of International Proceedings, 2020)
The agri - food industries are of particular strategic interest for many governments. Policy changes in this area have direct implications for consumers, landscapes and the environment. The aim of the article is to analyse the intra EU-28 agri – food trade in the context of the EU internal policies. The dynamics of the intra EU-28 agri – food trade was analysed in terms of the changeability and differences if compared to the previous periods. The general trend line was built using the appropriate function (choosing from the exponential, linear, logarithmic, polynomial, and power functions) taking into consideration the value of the R² coefficient. With the help of one of the functions mentioned above, the projection of the intra EU-28 agri – food trade amount for the following two periods was made. The comparative structural analysis of the intra EU-28 agri - food imports and exports structure in 2019 showed, that the imports structure doesn’t differ a lot from that of the exports one. The analysis of the intra EU-28 agri – food trade and its projections made for the following two years point to the successful implementation of the EU internal policies in general and the European Single Market and European Monetary Union in particular. It is also thanks to the worldwide reputation of EU products as being safe, sustainably produced, nutritious and of high quality. The data analysed in the article were taken from the Eurostat official web page. The time frame under research is 15 years – from 2005 to 2019 included.
Keywords: Intra EU-28; agri – food trade; EU internal policies.